TINGKAT KESIAPAN IMPLEMENTASI KNOWLEDGE MANAGEMENT PADA DIVISI TEKNOLOGI INFORMASI PT. “X” - Dwi Atmodjo Wismono Prapto; Sumiati Hutagalung (Jurnal Sistem Informasi, 2016)
IT Consultants are in the need of knowledge resources from experts who have either tacit, implicit, or explicit. Hence, a system that is able to manage knowledge (Knowledge Management/KM) is required. Along with success stories and failure experienced by many organizations in the implementation of KM system, it indicates that there should be factors that have roles in determining the successes of KM implementation. These factors are highly related to the readiness of the institution or company. Therefore, before implementing KM, it is necessary to analyze the readiness of the institution or organization. Analysis of readiness is expected to give an overview to the management about the state of readiness and aspects related to the successful implementation of KM. This study aims to measure the readiness of KM implementation in IT division in one of the IT consultation firm. The measurement of readiness was based on the extraction results of previous studies from which seven research aspects are obtained to be analyzed. Those aspects are strategy, organization, culture, technology, motivation, process, and human resources. Data was collected by questionnaires while data analysis was performed using descriptive statistical analysis. The analysis showed that the overall implementation of KM in IT division reached a readiness level of 2.26 in implementing KM.